Functional Somatic Symptoms in Children and Adolescents A Stress-System Approach to Assessment and Treatment - Kozlowska, Kasia (Palgrave Texts in Counselling and Psychotherapy, 2020)
This open access book sets out the stress-system model for functional somatic symptoms in children and adolescents. The book begins by exploring the initial encounter between the paediatrician, child, and family, moves through the assessment process, including the formulation and the treatment contract, and then describes the various forms of treatment that are designed to settle the child's dysregulated stress system. This approach both provides a new understanding of how such symptoms emerge - typically, through a history of recurrent or chronic stress, either physical or psychological - and points the way to effective assessment, management, and treatment that put the child (and family) back on the road to health and well-being.